2001
DOI: 10.1021/jp013161d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Chemical Structure on Poly(methyl methacrylate) (PMMA) Surface Studied by Sum Frequency Generation (SFG) Vibrational Spectroscopy

Abstract: The molecular chemical structure of poly(methyl methacrylate) (PMMA) surface has been studied by sum frequency generation (SFG) vibrational spectroscopy. By using various methods, we have shown that reflected SFG spectra of PMMA collected in our experiments only come from the polymer/air interface, not from the polymer/substrate or the bulk polymer. These SFG spectra are dominated by the vibrational bands from the ester methyl group. Ranges of orientation and orientation distribution of the ester methyl group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
537
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(556 citation statements)
references
References 49 publications
19
537
0
Order By: Relevance
“…21,25,53,58,68,106 Here we can show that these values are actually quite reasonable approximation of the common simple molecular groups such as -CH 3 , -C=O, etc. at the interface.…”
Section: 103supporting
confidence: 51%
See 1 more Smart Citation
“…21,25,53,58,68,106 Here we can show that these values are actually quite reasonable approximation of the common simple molecular groups such as -CH 3 , -C=O, etc. at the interface.…”
Section: 103supporting
confidence: 51%
“…Close inspection shows that the orientational angle thus obtained is actually inconsistent with other studies. 102,103,105,106 Therefore, whether the same n ′ = 1.18 value is suitable for the three groups needs to be re-examined. In a recent study in our research group, using a self-consistent approach we found that the n ′ (800nm) ∼ 1.5 and n ′ (400nm) ∼ 2.5 for the -(C 6 H 4 ) 3 -CN chromophore from the SHG data, significantly different from that of the -CH 3 or -CN group, and consistent with the large polarizability of the -(C 6 H 4 ) 3 -CN chromophore.…”
Section: 77mentioning
confidence: 99%
“…It is challenging to determine a unique solution for the average tilt angle and its distribution using the SFG results. 6 In addition to these three main parameters, the overlapping of hydrocarbon peaks in the SFG spectra in the wavenumber range from 2800 to 3100 cm −1 can also influence the interpretation of the SFG results. Because of these complications, it is difficult to directly use the SFG results to determine the surface composition and orientation of chemical groups on the surface of polymeric materials, especially in the case of PMMA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Especially, it has been used as bone cement, 20 in intraocular lenses, 21 and as a drug delivery material, 22 where understanding the surface molecular structure is of great importance. The surface of PMMA was characterized using SFG by Chen et al, 6 and the SFG spectra in SSP (s-polarized SFG, s-polarized visible, and p-polarized IR) polarization combination showed a dominant peak at 2950−2955 cm −1 , which was assigned to the ester-methyl side chain of PMMA and indicated ordered ester-methyl groups tilting toward surface normal. Further analysis led the authors to conclude that the α-methyl groups tend to lie down in surface plane and as a result were not observed in the SSP spectra.…”
Section: ■ Introductionmentioning
confidence: 99%